The Role of Bank Indonesia's Digital Financial Literacy in Preventing Financial Crimes in Banten Province - Saputra, Izul; Fitriyah, Neka; Winangsih, Rahmi (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Financial technology (fintech) has expanded access to financial services in Indonesia but has also heightened risks of digital crimes such as identity theft, online fraud, phishing, and malware attacks. In Banten Province, the rapid growth of fintech platforms is coupled with low digital financial literacy, making the public more vulnerable. This study examines the role of Bank Indonesia's digital financial literacy in preventing financial crimes in Banten Province using a qualitative approach with interviews, observations, and documentation studies, analyzed thematically. Findings reveal that the Bank Indonesia Banten Representative Office plays a strategic role through three main functions: (1) as a regulator emphasizing literacy as early prevention; (2) as a facilitator conducting educational programs directly and online; and (3) as a supervisor monitoring and evaluating program effectiveness. Digital financial crimes in the region have risen in both frequency and complexity, with perpetrators exploiting low literacy through phishing, illegal loans, impersonation of official institutions, and emotional manipulation. This highlights digital literacy as a primary community safeguard. In Serang City, the literacy program is delivered through seminars, training, workshops, transaction simulations, and digital channels such as social media, webinars, and educational videos. The inclusive approach is tailored to varying levels of understanding and targets students, MSMEs, and the elderly, ensuring broad community engagement in crime prevention.